Analyzing the Profitability Determinants: Evidence from Chinese Banks, 2016 to 2020 - Chen, SiHao (2022)
The reform of Chinese banking industry has imposed a profound effect on banks profitability in the recent decade. Among these actions of reform, we believe the reform of interest rate liberalization is one of the most important reforms in the recent five years. In this paper, we conduct a research on determinants of profitability for Chinese banking industry over year 2016 to 2020. Two methods are applied to the study which are fixed effect estimation and two step system Generalized Method of Moment (S-GMM). We found that smaller banks with lower equity to assets ratio, lower credit risk and better cost management tend to outperform those banks with higher equity to assets ratio, higher credit risk and poor cost management. We also found a positive and significant correlation between z score and bank profitability, taxation was also found to be positively correlated with bank performance but only with minor effect. Most importantly, we found an evidence that joint-stock commercial banks(JSCBs) tend to outperform other types of banks and a negative shock brought by the COVID-19 to the banks profitability. This shock is especially obvious in 2020.